A chiral polymer as chromo-fluorescence and CD response sensor for specific recognition of fluoride. (February 2017) - Bai, Jianwei; Yin, Hongyan; Zhang, Yunan; Zhang, Chunhong; Liu, Lijia; Xu, Xiaodong
Graphical abstract: Highlights: A novel phenylglycine-bearing optically active monomer ( SS -PEBM) is synthesized. The poly( SS -PEBM) shows high selectivity for F − relative to other anions. 1 H NMR titration experiments indicate the mechanism of the polymer probe to F − . The CD response of chiral poly( SS -PEBM) offers a new channel to recognize F − . Abstract: A new kind of polymeric chemosensor containing chiral phenylglycine and 1-phenethylamine moieties in the side chain was synthesized by reversible addition-fragmentation chain transfer (RAFT) polymerization, which can guarantee controllable molecular weight, narrow molecular weight distribution, and precise polymer structure. As a chemosensor, the resulting polymers showed UV–vis and fluorescence spectra changed upon addition of F − relative to other anions including Cl −, Br −, HSO4 −, AcO −, NO3 −, H2 PO4 −, and N3 − . When F − was added at high concentrations, the polymer gave detectable color change from colorless to yellow, which was attributed to the deprotonation process of the acylamino NH group and the mechanism was supported by the 1 H NMR titration. Furthermore, the addition of F − also can lead to a most pronounced change of CD spectra of the chiral polymer, indicating this kind chiral sensor can also be used as a probe for selective recognition of F − based on CD spectra.